OPTIMIZATION OF SURGICAL TREATMENT METHODS FOR BENIGN TUMORS OF THE PAROTID GLAND USING PRECISION TECHNIQUES - Akhrorov Alisher Shavkatovich (Journal of Applied Science and Social Science, 2026)
Benign tumors of the parotid gland represent the most common neoplasms of the salivary glands and require precise surgical management to ensure complete removal while preserving facial nerve function. This study aims to optimize surgical treatment methods through the application of precision techniques, including intraoperative nerve monitoring, microsurgical dissection, and minimally invasive approaches. A mixed-methods research design combining quantitative and qualitative analyses was employed. Clinical outcomes of 86 patients undergoing conventional and precision-based surgeries were compared. The results demonstrate that precision techniques significantly reduce postoperative complications, particularly facial nerve paresis, and improve aesthetic and functional outcomes. Qualitative data obtained from patient interviews further confirm enhanced satisfaction and quality of life. Statistical analysis reveals a decrease in complication rates from 22% in traditional methods to 9% in precision-guided procedures. The study concludes that integrating precision techniques into parotid surgery protocols enhances surgical safety and efficacy, offering a promising direction for future clinical practice and research in head and neck surgery.